2011
DOI: 10.1002/ptr.3380
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effect of n‐Butanol Extract from Asparagus officinalis L. in Mice fed a High‐fat Diet

Abstract: During industrial processing of Asparagus (Asparagus officinalis L.), around half of each spear is discarded. However, these discarded asparagus (by-products) might be used as food supplements for their potential therapeutic effects. This study evaluated the hypolipidemic effect of n-butanol extract (BEA) from asparagus by-products in mice fed a high-fat diet (HFD). Continuous HFD feeding caused hyperlipidemia, oxidative stress and liver damage in mice. Interestingly, while BEA significantly decreased the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Asparagus has been used in traditional Asian medicine since ancient times for its diuretic, antifatigue, and metabolism‐enhancement effects. Recent studies demonstrated that asparagus extract modulates blood glucose level in diabetic rats (Hafizur and others ) and has hypolipidemic action (Zhu and others ) as well as oxidant defense activity (Kim and others ). The current study was performed to identify the enhanced expression of intracellular heat shock protein 70 (HSP70) in response to a unique ETAS and its antistress effect.…”
Section: Resultsmentioning
confidence: 99%
“…Asparagus has been used in traditional Asian medicine since ancient times for its diuretic, antifatigue, and metabolism‐enhancement effects. Recent studies demonstrated that asparagus extract modulates blood glucose level in diabetic rats (Hafizur and others ) and has hypolipidemic action (Zhu and others ) as well as oxidant defense activity (Kim and others ). The current study was performed to identify the enhanced expression of intracellular heat shock protein 70 (HSP70) in response to a unique ETAS and its antistress effect.…”
Section: Resultsmentioning
confidence: 99%
“…Asparagus butanol [196][197][198] extract significantly decreased the levels of body weight gain, serum total cholesterol and low density lipoprotein cholesterol; it dramatically increased the high density lipoprotein level when administered at three different doses (40, 80 or 160 mg/kg body weight) for 8 weeks in hyperlipidemic mice. In addition, asparagus butanol extract decreased the levels of alanine transaminase, aspartate transaminase and alkaline phosphatase in serum.…”
Section: Asparagus Officinalismentioning
confidence: 93%
“…Fuentes-Alventosa et al (2009) reported that high dietary fiber powder obtained from asparagus by-product exhibited antioxidant activity. The results from our laboratory showed that aqueous, ethanolic and n-butanol extracts from residue of asparagus woody stems (juice removed) displayed hypolipidemic property in hyperlipidemic mice (Zhu et al 2010(Zhu et al , 2011, and the aqueous extract was also found to exhibit hypoglycemic activity in diabetic rats (Zhao et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…The results from our laboratory showed that aqueous, ethanolic and n‐butanol extracts from residue of asparagus woody stems (juice removed) displayed hypolipidemic property in hyperlipidemic mice (Zhu et al . , ), and the aqueous extract was also found to exhibit hypoglycemic activity in diabetic rats (Zhao et al . ).…”
Section: Introductionmentioning
confidence: 99%